Markerless motion capture system - Mündermann, L.; Corazza, S.; Andriacchi, T. P. (2008)
A method of generating a three-dimensional dynamic model of a single subject moving within a volume, comprising: (a) defining a static full-body model R of said single subject, wherein said model R is a three-dimensional articulated multi-segment model defined by polygon meshes for the body segments, wherein said articulation is defined by three-dimensional joint centers with soft joint constraints between the neighboring body segments in said articulated multi-segment model providing up to 6 degrees of freedom (DOF) in articulation at each joint; (b) markerless motion capturing, with a multiple camera system, a three-dimensional representation of said single subject moving within said volume; (c) defining for each of said markerless-motion-captured frames a three-dimensional full-body model C of said single subject; (d) matching said full-body model C of each of said markerless-motion-captured frames with said full-body model R, wherein said matching allows for deviations between the neighboring body segment using soft joint constraints; and (e) outputting for each of said markerless-motion-captured frames a full-body three-dimensional model of said single subject for the movement within said volume, wherein said full-body three-dimensional model is a three-dimensional articulated multi-segment model with three-dimensional soft-joint constraints providing up to 6 DOF in articulation at each joint.